Pengaruh Larutan Hara dan Pupuk Organik Cair Urin Kelinci terhadap Pertumbuhan Pakcoy (Brassica rapa L.) pada Teknik Hidroponik - Iqlima, Selesa; Rachmawati, Diah (Bioscientist : Jurnal Ilmiah Biologi, 2023)
The demand for pakcoy (Brassica rapa L.) a nutritious vegetable is increasing without being balanced due to the limited of agricultural land. The Wick system hydroponic cultivation technique can be a solution to increase pakcoy productivity. AB mix hydroponic nutrient solution is difficult to reach because it is expensive and has a negative impact on plants. It can be combined with rabbit urine LOF to provide essential nutrients for plants. This research aims to determine the effect of the combination of AB mix with LOF rabbit urine on the growth of pakcoy plants. The research design is CRD, 1 factor, 8 treatments, and 3 replications. Treatments include A1P0=AB mix 100% +0mL/L LOF rabbit urine, A1P1=AB mix 100% + 1mL/L LOF rabbit urine, A1P2=AB mix 100%+2mL/L LOF rabbit urine, A1P3=AB mix 100% +3 mL LOF rabbit urine, A2P0=AB mix 75%+0mL LOF rabbit urine, A2P1=AB mix 75%+1mL/L LOF rabbit urine, A2P2=AB mix 75%+2mL/L LOF rabbit urine, and A2P3=AB mix 75%+3mL/L L of rabbit urine.The addition of rabbit LOF gave the best results with AIP3 treatment on growth parameters, plant height, number of leaves, leaf area, fresh weight of shoots, and roots, dry weight of shoots and roots, respectively 27.41 ± 1.44 cm, 17.33 ± 0.95 pieces 632.89±228.20cm2, 61.88±13.42g, 1.648±0.374g, 3.132±0.614g, and 0.101±0.021g. The essential nutrient content of rabbit urine LOF increases the availability of internal nutrients which are influenced by metabolism, absorption capacity, water and sunlight.